Autonomous movement, root location and infection by sporangial and cyst derived zoospores of Phytophthora cryptogea isolates in water - K.B. KHARE*, D.O. OTAYE, S.L. VON BROEMBSEN, (Indian Phytopathology, 2010)
The ability of cyst derived zoospores (CDZs) and sporangial derived zoospores (SDZs) to move autonomously in water in model mazes and linear troughs and to infect roots of vinca ( Catharanthus roseus) seedlings at fixed distances from a point of introduction were assessed at 4 h for two isolates of Phytophthora cryptogea (FWDM4 and FDM51). The study showed that both CDZs and SDZs infected roots at distances up to 215 mm (in model mazes) and 320 mm (in linear troughs), and were also able to move the same distances in controls without seedlings. A concentration of 104 zoospores/ml when used at the point of introduction in linear troughs, SDZs and CDZs of the isolate, FDM51 moved actively and infected roots to a distance of 320 mm. SDZs and CDZs of FWDM4 infected seedlings at distances of 240 mm and 320 mm respectively and both the isolates were recovered at 320 mm without seedlings. The results indicate that the CDZs of Phytophthora cryptogea can serve as effective dispersal and infection units in water and suggests that zoospores may be able to move autonomously to greater distances in a non-restraining medium than previously thought.